The Relationship between Self-Efficacy and Science Anxiety with Science Literacy Among Senior High School Students in Biology Learning - Dhila Rallyta; Ruswan; Tauhidah, Dian (Bioeduca : Journal of Biology Education, 2025)
Scientific literacy is a crucial competency in the 21st century, particularly in understanding scientific issues, evaluating associated risks and benefits, and making decisions based on scientific reasoning. However, the level of scientific literacy among students in Indonesia, including those at SMAN 6 Semarang, remains relatively low. Two psychological factors suspected to influence this condition are self-efficacy and science anxiety. This study aims to investigate the relationship between self-efficacy, science anxiety, and students’ scientific literacy. The research employed a non-experimental quantitative approach with a correlational design. The sample was selected using purposive sampling. Data were collected through tests and questionnaires: the self-efficacy questionnaire was developed based on indicators by Bosscher and Smit (1998), the science anxiety questionnaire was adapted from the Abbreviated Science Anxiety Scale (ASAS) by Megreya et al. (2021), and the scientific literacy test items were constructed based on the 2025 PISA indicators. Data analysis included Pearson correlation, multiple correlation, and multiple linear regression. The results showed a significant relationship between self-efficacy and scientific literacy (p = 0.027; r = 0.174; contribution = 3%). Science anxiety also showed a significant relationship (p = 0.027; r = 0.173; contribution = 3%). Simultaneously, both variables significantly correlated with scientific literacy (p = 0.001; R = 0.281), contributing 6.7%, although the strength of the relationship was weak.